The syntax of Hungarian - Kiss, Katalin É (Cambridge syntax guides., 2002)
Clearly written and comprehensive in scope, this is an essential guide to syntax in the Hungarian language. It describes the key grammatical features of the language, focusing on the phenomena that have proved to be theoretically the most relevant and have attracted the most attention.